Health Risk Assessment of Gaseous Pollutants in the Ambient Environment of Rayong City, Thailand: The Initiative of the EEC Area - Kawichai, Sawaeng; Sillapapiromsuk, Sopittaporn; Bootdee, Susira (Applied Science and Engineering Progress, 2023)
The Eastern Economic Corridor (EEC) project initiative has an adverse impact on the increasing problem of air pollution. This research aims to determine ambient NO2, O3, and SO2 levels in the industrial area (IT) and urban area (UB) in Rayong city as part of a health risk assessment from 2018 to 2020. The average NO2, O3, and SO2 concentrations at IT site were ranged from 23.5–24.7 μg/m3, 42.7–56.7 μg/m3, and 12.5–14.0 μg/m3, while those at UB site were 14.8–20.7 μg/m3, 42.5–68.3 μg/m3, and 3.2–4.7 μg/m3, respectively. Their concentrations in dry season were higher than those in wet season at both IT and UB sites. The days in the IT site exceeded the daily WHO guideline of NO2 was 34.8–44.0%, while those in the UB site were 10.8–34.5%. The hazard quotient (HQ) values for a non-carcinogenic risk to human health caused by NO2 exposure indicated a medium hazard (HQ = 1.1–10.0), whereas the HQ values for SO2 and O3 indicated a negligible risk (HQ < 1.0). The total non-carcinogenic risk (HI) from air pollutants contamination being exposed concurrently, on the other hand, indicated risk levels that are likely to affect health, particularly children. Therefore, environmental management and protection in Rayong city are important for people who live in industrial and urban areas, especially during dry period.